Warming increases the relative change in the turnover rate of decadally cycling soil carbon in microbial biomass carbon and soil respiration - Liu, Dan; Zhang, Wenling; Xiong, Chunmei; Nie, Qingyu (Frontiers in Earth Science, 2023)
Decadally cycling soil carbon (dSOC) is the main component of the terrestrial soil carbon (C) pool. The response of dSOC to warming largely determines the feedback between climate warming and the C cycle. However, there is a lack of investigations about the effect of warming on the relative change in turnover rate (RCT) of dSOC and annually cycling SOC (aSOC) in dissolved organic carbon (DOC), microbial biomass carbon (MBC) and CO2. We clarified this issue by incubating two C3-C4 vegetation switch soils (23 years switch, HA soil and 55 years switch, GG soil) at 20 and 30 oC in the recently improved continuous airflow CO2 trapping system for one year. Warming increased the contribution of dSOC (C3-C) by 21℅ (soil HA) and 8℅ (soil GG) in MBC, and 38 ℅ (soil HA) and 15 ℅ (soil GG) in CO2, while only 2-3℅ increase in DOC at the final stage of the incubation. Furthermore, warming increased the RCT in MBC and CO2 by 5.3- and 4.1-fold, respectively, but had no significant influence on the RCT in DOC, indicating that soil microbes may be an important engine to accelerate dSOC-derived CO2 emission in a warming world.